A Study of EDI, Processes, Operations and How Employees are Motivated at a Kenyan Bank - Fazal, Waheed Sultanali Muradali (2009)
According to Brabston, L. and Porter, (2004) Information system (IS) and business strategy are essential facets in any organization particularly a bank, we are interested in this sector because it is a major component in Kenya‟s growing economy and so far hardly any research has been done on the efficiency of a Kenyan banks. This dissertation concentrates on a small service enterprise and how IS/IT as well as work motivation strategy can influence the business strategy; we also study how the bank stays in constant communication with the head office. How the staff initiates and maintains motivation which turn helps the bank achieve profits is the other part of this dissertation. A small branch of a bank (referred to as Imperial Mombasa in this dissertation) which has approximately 10-60 employees was selected for the case study. Generally speaking, IS comes about when interrelated components work together to collect, process, store and distribute information. Most enterprises around the world use a computer-based form known as Electronic Data Interchange (EDI); in this dissertation, we use the abbreviation EDI due to its simplicity. To run an IS; the enterprise needs information technology (IT). IT is the hardware which is connected to the IS, such as computer, servers, computer network material etc (Brandt, C. and Lindberg, R., 2006). The latter part looks at how imperial needs motivated employees to sustain growth and offer better services to their clients (the bank‟s staffs are taken into context). Again many managers nowadays are not aware of the effects that motivation can have on their business. Therefore, it is essential that they learn and understand the importance of the factors that determine positive motivation in the workplace (Frey, B. and Osterloh, M., 2002). It is also important for the company‟s well being to find ways of encouragement and sustaining fundamental motivation. But motivating people is normally easier said than done. Employees cannot be programmed to embrace the company‟s objectives very easily. At the moment, many employers are focusing to motivate the employees by means of monetary incentives. However, these techniques of motivations are not always enough to keep employees motivated, and essential motivation is very important in ensuring companies achieve their major goals. Extrinsic motivation satisfies indirect needs, which are unrelated to the task they are performing. Intrinsic motivation on the other hand satisfies direct needs, which aspires the people to perform a particular task,intrinsic motivation comes from carrying out an activity rather than from the result of an action (Beswick, D., 2006). According to Bateman, T. and Frey, B. (2001) job tasks are intrinsically motivating when motivators like the responsibility involved in their job, the challenges at work, the achievement in the work, the amount of skill variety, and advancement opportunity. One of the key functions of an organization is therefore ensuring the correct form of motivation is used in the organization. It is also crucial for management to focus on the right ways of motivating the employees so that the company can use its shared resources as effectively as possible (Beswick, D., 2006). It is very important for management to have knowledge about the ways the employees are motivated; by monetary incentives or by internal factors like recognition and challenge at work. The employees‟ are the company's greatest assets and no matter how efficient is the company‟s technology or machinery; the effectiveness and efficiency of a company staff cannot be replaced.